THE IMPORTANCE OF INTERACTIVE METHODS IN DEVELOPING STUDENTS’ COMMUNICATIVE COMPETENCE (International journal of artificial intelligence, 2025)
This article explores the role and significance of interactive methods in developing students’ communicative competence within the modern educational process. Communicative competence is understood as an individual’s ability to express thoughts clearly, accurately, and appropriately in both oral and written forms, to understand others’ messages, and to participate effectively in social interaction. The study emphasizes that interactive teaching strategies create a supportive and dynamic environment that enhances students’ confidence, initiative, and collaboration skills. Methods such as “Brainstorming,” “Cluster,” “Role play,” and “Debate” stimulate verbal fluency, quick thinking, and active participation in group discussions. The use of these techniques fosters students’ speech culture, reflective abilities, and social adaptability, thereby improving the overall quality of education.